Tribochemical synthesis of functionalized covalent organic frameworks for anti-wear and friction reduction - Xiaozhi Zhang; Qi Lu; Yaojie Yan; Tingting Zhang; Shujuan Liu; Meirong Cai; Qian Ye; Feng Zhou; Weimin Liu (Friction, 2023)
Abstract Tribochemistry can be defined as a field dealing with the chemical reactions occurring in the friction zone, capable of catalyzing mechanical and physico-chemical changes in the friction contact area, facilitating the formation of tribo-films, which is also an efficient approach to fabricate novel innovative materials. In this paper, we report the successful synthesis of the silicon oil (SO)-functionalized covalent organic frameworks (COFs) prepared via the tribochemical method when subjected to the reciprocating friction; during the friction process, the rich aldehyde-terminated COFs can bond with amino SO via the Schiff base reaction between aldehyde group and amino group to obtain the desired functionalized COFs (SO@COF-LZU1). The tribochemical reaction progress was tracked through in-situ monitoring of the friction coefficient and the operating conditions during the entire friction process. Noticeably, the friction coefficient continued to decrease until it finally stabilized as the reaction progressed, which revealed the formation of a protective tribo-film. Herein, an approximate tribochemical model was presented, wherein the reaction mechanism was investigated and analyzed by employing structural analysis techniques like magic angle spinning nuclear magnetic resonance (MAS NMR), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Furthermore, the tribochemical-induced SO@COF-LZU1 exhibited remarkable tribological performance with a low friction coefficient of 0.1 and 95.5% reduction in wear volume when used as additives of 500SN base oil. The prime focus of our research was on the preparation and functionalization of COF materials via tribochemical reactions, unraveling a new avenue for the rational design and preparation of functional materials.